Portrait de l’artiste en jeune barbu : Le Peintre de Saltzbourg de Charles Nodier - Sukiennicka, Marta (Acta Universitatis Lodziensis. Folia Litteraria Romanica, 2019)
Charles Nodier was one of the leading advocates of the fraternity of artists in the 1830s, but his experience of life and work in artistic circles embracing writers, painters and composers was not limited to his own literary salon at the Arsenal. Already as a young man, Nodier moved in the circle of Méditateurs, a group started at the beginning of the 19th century by rebellious former students of Jacques-Louis David. This experience left its mark on Nodier’s work: his novel, Le Peintre de Saltzbourg (1803) reveals a certain affinity with the aesthetic doctrines of Maurice Quai and Méditateurs. This forgotten episode of the history of Romanticism was brought back to memory in 1832 by the republication of the novel in OEuvres de Charles Nodier, and by the contemporary critics, who compared Méditateurs to Jeunes-France, a popular artistic cenacle of the day.